2019
DOI: 10.1136/lupus-2019-000342
|View full text |Cite
|
Sign up to set email alerts
|

Global consensus building and prioritisation of fundamental lupus challenges: the ALPHA project

Abstract: ObjectiveLupus is a complex, heterogeneous autoimmune disease that has yet to see significant progress towards more timely diagnosis, improved treatment options for short-term and long-term outcomes, and appropriate access to care. The Addressing Lupus Pillars for Health Advancement (ALPHA) project is the first step in establishing global consensus and developing concrete strategies to address the challenges limiting progress.MethodsA Global Advisory Committee of 13 individuals guided the project and began bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…While there have been advances in understanding disease mechanisms and treatment of cSLE in the last decade, significant needs remain, underscoring the necessity of a focused research agenda for allocation of available resources. Expanding on the findings from the ALPHA study5 6 and CARRA-LFA survey regarding cSLE research priorities,7 we elucidated approaches to address cSLE research priorities, exploring both barriers and opportunities to advancing cSLE research. Multidisciplinary experts in our study identified research priorities represented by five domains: (1) expanding disease knowledge; (2) investigator collaboration; (3) partnering with patients and families; (4) improving care to optimise research; and (5) overcoming investigator barriers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there have been advances in understanding disease mechanisms and treatment of cSLE in the last decade, significant needs remain, underscoring the necessity of a focused research agenda for allocation of available resources. Expanding on the findings from the ALPHA study5 6 and CARRA-LFA survey regarding cSLE research priorities,7 we elucidated approaches to address cSLE research priorities, exploring both barriers and opportunities to advancing cSLE research. Multidisciplinary experts in our study identified research priorities represented by five domains: (1) expanding disease knowledge; (2) investigator collaboration; (3) partnering with patients and families; (4) improving care to optimise research; and (5) overcoming investigator barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Although paediatric rheumatologists were included in both the initial interview and survey components, only 6% of survey respondents primarily practised paediatric rheumatology. Responses of phase I of the ALPHA survey indicated that the lack of attention to paediatric issues is a barrier to SLE drug development and clinical care 5 ; however, specific aspects of these issues were not detailed. Subsequently, phase II of the ALPHA study proposed actionable solutions to the identified research barriers from phase I of the study.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed, disease heterogeneity is perhaps the most significant obstacle to progress. Other barriers to advancement are lack of diagnostic, predictive, prognostic, and drug-response biomarkers; ineffective management of SLE due to social determinants of care in predominantly lower socioeconomic status areas; and lack of treatment adherence [ 24 ]. Nontraditional solutions to these challenges should be explored and digital therapeutics offer one such novel approach.…”
Section: Discussionmentioning
confidence: 99%
“…Widely variable initial presentation, disease course, organ involvement, and response to treatment complicate diagnosis, management, and clinical research efforts. An international team of experts have identified SLE heterogeneity as “the primary barrier hindering advancement” [ 24 ]. Given this heterogeneity, it is reasonable to hypothesize that numerous dietary, environmental, and lifestyle SLE triggers exist and differ from patient to patient.…”
Section: Introductionmentioning
confidence: 99%
“…Phase I, during which these barriers were identified, was completed in 2019. 9 As described in this article, the goals of phase II were to confirm the barriers, identify and reach consensus on actionable solutions to each barrier, and determine preliminary steps to implement these solutions. Figure 1 summarises the phases of the ALPHA Project.…”
Section: Introductionmentioning
confidence: 99%